Implementation of Problem-Oriented Learning Sessions in Para-Clinical years of Medical College - Saurabh RamBihariLal Shrivastava; Prateek Saurabh Shrivastava (Tabriz University of Medical Sciences, 2019)
Background: In order to develop competent health care professionals and to help medical students to acquire clinical reasoning, critical thinking and problem-solving skills, it was decided to initiate problem-oriented learning (POL) sessions as a part of implementation of integrated learning in the second year of undergraduate education of medical students in a medical college. Methods: A group of 150 students in the second year of their undergraduate education was divided into 10 sets of 15 members each. For each weekly POL session, one lead department was identified and from that department, one faculty member was assigned for each of the 10 groups for clarity and guidance. Four to five departments in all were involved in these POL sessions based on the topic and were instructed to frame their objectives and share these with the lead department at least one week prior to each session to develop appropriate problems for discussion. Results: Initial results failed to meet the desired objectives. The entire exercise was restructured and attention was given to the areas where weaknesses were identified. Faculty members were provided with additional information about POL and the number of sessions was reduced to two per month. Faculty members were instructed to be discussion facilitators rather than to become involved in didactic teaching. Subsequently, a significant improvement was observed both in terms of outcomes and student participation. Conclusion: It is relatively easy to start a new mode of teaching-learning; however, outcomes improve when efforts are planned systematically and implementation is revisited after challenges and gaps are identified.